Urban (Digital) Play and Right to the City: A Critical Perspective - Castro Seixas, Eunice (Frontiers in Psychology, 2021)
In this paper I discuss the concept of the right to the city in articulation with the concept of urban play and more specifically, the diverse body of research related with playable and playful cities. Following a brief review of these two concepts and related studies, I critically discuss the possibilities of articulating Lefebvre’s radical concept of the right to the city to contemporary interventions on urban and digital play.